Flavonoids hydroxyl group position effect on inducing ssDNA damage mediated by cupric ions - Elmegerhi, Suad Ahmed, author; Kato, Takamitsu, advisor; Bailey, Susan, committee member; Thamm, Douglas H., committee member; Boss, Mary-Keara, committee member (Colorado State University. Libraries, 2020)
To view the abstract, please see the full text of the document.
Keywords: DNA damage; hydroxyl groups position; flavonoids; cupric ions